DAMPAK KULTURSTELSEL TERHADAP KEHIDUPAN SOSIAL EKONOMI DI DAERAH PACITAN PADA ABAD XIX - Iswahyudi Iswahyudi (Jurnal Penelitian Humaniora, 2000)
Abstract The purpose of this research was to reconstruct the Culturstelsel implementation in Afdeling Pacitan during 19th century. The background of this study was the issue of Cultuurstelsel causing poverty for the people, however in Afdeling Pacitan Culturstelsel improved the welfare of the people. That positive impact was resulted from the internal factors, such as: the large number of land workers and the type of plant matched with the land. The external factors were that the land rent or land tax policy tended to reduce as substituted by the coffee price. This welfare condition was also supported by the native coffee plantation  or “kopi pagar” that was not a commercial crop categories. Keywords: Cultuurstelsel, penanaman coffee, social change